Metallurgical characteristics of aluminum-steel joints manufactured by rotary friction welding: A review and statistical analysis - Hossein Ghari; Aboozar Taherizadeh; Behzad Sadeghian; Behzad Sadeghi; Pasquale Cavaliere (Journal of Materials Research and Technology, 2024)
Rotary friction welding (RFW) is a solid-state joining process that can be used to join different alloy systems such as aluminum-steel alloys. Rotary friction welding has become increasingly appealing for various industries due to the sustainable advantages that it offers, including overall cost reduction, weight minimization, and unique properties. However, the formation of brittle intermetallic compounds (IMCs) at the interface can be a challenge in the welding process of aluminum-steel alloys. This paper reviews the metallurgical characteristics of aluminum-steel alloy joints manufactured by rotary friction welding. The different types of intermetallic compounds that can form at the interface, as well as the factors that affect their formation, are discussed. The effects of rotary friction welding parameters on the microstructure and mechanical properties of the joints are also presented. Specifically, minimizing interfacial reaction layers via post-weld heat treatment and controlling the heat input during the process is crucial to suppressing the formation of intermetallic compounds. This study employed artificial intelligence modeling, specifically the artificial neural network - multilayer perceptron, to investigate the effect of various parameters on the ultimate properties of the parts welded together. Overall, this paper provides an excellent resource for industries looking to embrace rotary friction welding to tackle the challenge of dissimilar Al-steel joining.